PENGARUH JUMLAH PENDUDUK, JUMLAH INDUSTRI DAN PDRB TERHADAP PENERIMAAN PAJAK DAERAH DI KABUPATEN SUMENEP TAHUN 2006 – 2011 - Arifin, Miftahol; Rofik, Mohammad; Andrianingsih, Very (PERFORMANCE: Jurnal Bisnis & Akuntansi, 2018)
This research is a quantitative descriptive Revenue Regional Tax Sumenep underthe title "Pengaruh Jumlah Penduduk, jumlah Industri dan PDRB terhadap PenerimaanPajak Daerah di Kabupaten Sumenep Tahun 2006 – 2011". The purpose of this studywants to know influence of the population, the total of large and medium industries, theamount of Gross Regional Domestic Product (GRDP) of the Local Tax Revenue SumenepYear 2006 to 2011. This study uses quartal time series data from 2006 to 2011. Themethod of analysis using linear regression analysis with the validity of the classicalassumption, so the regression results can be validated at yield. The results usingregression data by the following equation: Y = 5.08E09 – 23968.50X1 - 20595.21X2 +2417.432X3 + 5889. Meaning X1 (Population) has a negative relationship with the localtax revenue Sumenep, X2 (Tolal of Large and Medium) has a negative relationship withthe local tax revenue Sumenep and X3 Domsetik Gross Regional Product Number (GDP)has a positive relationship to the tax revenue Sumenep area. Simultaneously by using thet test and the X3 X2 X1 variables have a significant influence to Sumenep Revenue taxes.so testing Fstatistik partially by test also showed that the variables of population, thenumber of medium and large industries as well as Gross Regional Domestic Product(GRDP) a significant effect on local tax revenues Sumenep. It was proved by F-statistikvalue > F table, 191.068 > 3.4668 with α of 5%. The conclusion of this study is avariable number of residents, the total of medium and large industries as well as GrossRegional Domestic Product (GRDP) a significant effect on local tax revenues Sumenep.